Phylogeographic history of mitochondrial haplogroup J in Scandinavia. Issue 2 (23rd November 2022) - Kristjansson, Dana; Schurr, Theodore G.; Bohlin, Jon; Jugessur, Astanand
Abstract: Background: Mitochondrial DNA haplogroup J is the third most frequent haplogroup in modern‐day Scandinavia, although it did not originate there. To infer the genetic history of haplogroup J in Scandinavia, we examined worldwide mitogenome sequences using a maximum‐likelihood phylogenetic approach. Methods: Haplogroup J mitogenome sequences were gathered from GenBank ( n  = 2245) and aligned against the ancestral Reconstructed Sapiens Reference Sequence. We also analyzed haplogroup J Viking Age sequences from the European Nucleotide Archive ( n  = 54). Genetic distances were estimated from these data and projected onto a maximum likelihood rooted phylogenetic tree to analyze clustering and branching dates. Results: Haplogroup J originated approximately 42.6 kya (95% CI: 30.0–64.7), with several of its earliest branches being found within the Arabian Peninsula and Northern Africa. J1b was found most frequently in the Near East and Arabian Peninsula, while J1c occurred most frequently in Europe. Based on phylogenetic dating, subhaplogroup J1c has its early roots in the Mediterranean and Western Balkans. Otherwise, the majority of the branches found in Scandinavia are younger than those seen elsewhere, indicating that haplogroup J dispersed relatively recently into Northern Europe, most plausibly with Neolithic farmers. Conclusions: Haplogroup J appeared when Scandinavia was transitioning to agriculture over 6 kya, with J1c being the most common lineage there today. Changes in the distribution of haplogroup J mtDNAs were likely driven by the expansion of farming from West Asia into Southern Europe, followed by a later expansion into Scandinavia, with other J subhaplogroups appearing among Scandinavian groups as early as the Viking Age. Abstract : Although the overall distribution of haplogroup J is relatively similar across several world regions, the subhaplogroup distributions are varied.